Effect of the Concrete Mesostructure Geometric Form on Its Elastic Modulus - Xu Yang (Advances in Civil Engineering)
A comprehensive understanding of the geometrical form of the concrete mesostructure is important because it is associated with the complex and random mechanical behavior of the concrete. There is still uncertainty about how to characterize the geometrical form of the concrete mesostructure and its effect on the observed macroscopic behavior. The coarse aggregate content and fractal dimension were used in this study to indicate the geometrical form of concrete at the mesolevel. Taking the mechanical parameters measured in experiments, a group of mesomodels with various fractal dimensions and coarse aggregate contents was simulated by using the random fractal modeling method and then was studied and discussed. The analytical solution, simulation, and experimental data all suggested that the elastic modulus increased with the increasing coarse aggregate content. Meanwhile, the fractal dimension can cause the elastic modulus to decline slightly. The comprehensive consideration of both fractal geometry and classical Euclidean geometry can aid in predicting the macroscopic behavior of concrete.